Karroyul (screenplay) - Scott, Kim (2015)
Karroyul is the tale of an Aboriginal girl who, feeling lost and empty after the death of her mother, discovers her past in an unlikely place. Accompanied into the bush by her uncle, Kelly soon finds that her surroundings are rich in Indigenous culture, with the stories of her ancestors waiting amongst the trees ready to be uncovered. Kelly comes face to face with her Aboriginal ancestry when her uncle Geoff takes her to a historical massacre site in rural Western Australia. Karroyul is a spiritual, coming-of-age journey adapted from the short story A Refreshing Sleep by Miles Franklin Award-winning Aboriginal writer Kim Scott and directed by Kelrick Martin Source: http://www.creativespirits.info/resources/movies/karroyul-returning#ixzz3o2szJt6Z